UPAYA JAKSA SELAKU EKSEKUTOR DALAM EKSEKUSI PUTUSAN PIDANA TAMBAHAN PENGEMBALIAN KERUGIAN KEUANGAN NEGARA AKIBAT TINDAK PIDANA KORUPSI ( Studi Pada Kejaksaan Tinggi Sumatera Barat ) - Hafri Sundhana (LPPM Universitas Ekasakti Padang, 2020)
The Prosecutor as a position granted by the law to execute the decision of a judge who already has permanent legal force is regulated in Article 1 (one) Item 1 (one) of Law Number 16 Year 2004 concerning the Attorney General of the Republic of Indonesia. Although the Prosecutor has attempted to save state finances by taking a number of legal actions in the form of payment of an amount of replacement money, in reality the state financial losses have not been returned to the quantity that should be or can be said to have not even the slightest amount of state financial losses successfully returned by the Executing Prosecutor. The issues raised in this thesis are: First, how is the effort of the prosecutor as the executor in executing additional criminal decisions to recover state financial losses due to criminal acts of corruption at the West Sumatra High Prosecutor's Office? Second, whether the legal consequences of the execution of the Additional Criminal Decision refund of State Financial Losses that have not been successfully carried out by the Prosecutor's Executor. Data sources used are secondary data and primary data. The data obtained were analyzed qualitatively and presented in a descriptive qualitative form. Based on the results of the discussion and analysis, it can be concluded as follows: First, the efforts made by the Executing Prosecutor in returning state financial losses due to corruption, include: (1) Making Declaration of payment of replacement money; (2) Tracing assets back; Second, the legal consequences of the execution of additional criminal decisions were not successfully carried out by the Executing Prosecutor, among others: (1) Submitting the case to the Datun section (Civil and State Administration) carried out in a civil suit through the State Attorney Attorney, and; (2) To serve a subsidair sentence in accordance with the content of a judge's decision that has permanent legal force.